Assessment of effectiveness of trainings conducted by ICAR - Vyas, A K; Jain, N K; Singh, Premlata; Satyapriya, Satyapriya; PauL, Sudipta; H V, Harish Kumar; Ray, Mrinmoy; Mohapatra, T (The Indian Journal of Agricultural Sciences, 2020)
Training is essential not only to increase productivity, but also to keep workers of an organization motivated and inspired. In this study, the effectiveness of trainings conducted by Indian Council of Agricultural Research (ICAR) during 2017-18 in which 901 Scientists, 506 Technical, 519 Administrative and 313 Skilled Support Staff (SSS) from 106 ICAR-Institutes across 26 States/UTs participated was assessed by HRM Unit, ICAR HQs, New Delhi during 2018-19. Study revealed that the pooled perceived training effectiveness index (PTEI) was 3.86, referring medium effectiveness of trainings. The mean PTEI score was the highest for SSS (3.94) followed by Administrative staff (3.90). Overall, most of the participants (58.83%) reported medium degree of effectiveness of the training programmes. Behavioural changes and changes in practices as a consequence of exposure to the trainings are evident from the findings. The study revealed that perceived effectiveness was significantly associated with age, gender and duration of training programmes. Some observed constraints by the trainees were inadequate infrastructure at Institutes, sometimes lesser relevancy of few topics and lack of practical exposure. The major suggestions were inclusion of more practical sessions, follow up programmes for trainee-trainer meet, and increasing the duration of the trainings in few cases. The trainings organised by ICAR should continue for all staff categories to bring about desirable changes in competencies.